Аналіз особливостей Character.AI: проблема довготривалої пам’яті у генеративному штучному інтелекті - Богдан, Н. І. (ХНУРЕ, 2025)
This work analyzes the capabilities and limitations of the Character.AI platform, which utilizes generative artificial intelligence to create interactive characters. The study highlights the growing popularity of AI-driven character generation among writers, game developers, and enthusiasts of interactive storytelling. Character.AI allows users to engage in virtual conversations with AI-generated personalities, enhancing creative experiences. The key advantages of Character.AI include its flexibility in character creation, interactive dialogue adaptation, support for role-playing scenarios, free accessibility, and a vast selection of pre-existing characters. These features make it a valuable tool for creative applications. However, despite its advantages, the platform has several notable shortcomings.
Keywords: Character.AI platform; довготривала пам'ять